Fundamentals of geomorphology (5th edition) - Mazurek, Małgorzata (Geologos, 2025)
Fundamentals of geomorphology (5th edition), by R.J. Huggett & E. Shuttleworth, 2023. Routledge, Taylor & Francis Group, 624 pages. Paperback: price 39.42, ISBN 978-1032169637.